Oral, Cloacal, and Hemipenal Actinomycosis in Captive Ball Pythons (Python regius) - Tillis, Steven B.; Iredale, Marley E.; Childress, April L.; Graham, Erin A.; Wellehan, James F. X.; Isaza, Ramiro; Ossiboff, Robert J. (Frontiers in Veterinary Science, 2021)
Ball pythons (Python regius) are one of the most commonly kept and bred reptiles in captivity. In a large ball python breeding colony, a unique syndrome characterized by granulomatous inflammation of the cloaca and hemipenes (phalli) was observed in 140 of 481 (29.1%) breeding males, but only one of 1446 breeding females. Lesions were absent in virgin males (n=201) and virgin females (n=293). On postmortem examination (n=13, 12 males, 1 female), numerous well defined mucosal and submucosal granulomas were present in the hemipenes (males) and cloaca (males and female). Extension into the coelomic cavity and liver was noted in a subset of these animals. An additional small subset of breeder animals (6/2027; 0.3%) presented with oral and mandibular swellings. Postmortem examination (n=4, all female) showed oral lesions histologically indistinguishable from the cloacal/hemipenal lesions. Aerobic bacterial culture of a hepatic granuloma of one snake resulted in the isolation of filamentous, fastidious, Gram-positive bacilli; amplification and sequencing of the 16S rRNA gene and subsequent phylogenetic analysis of the isolate identified the bacterium as a novel species of Actinomyces. Screening of cloacal and oral granulomas using a specific, heminested 16S rRNA PCR assay confirmed the presence of the agent in all 17 snakes, as well as in cloacal swabs taken at the time of necropsy in 11/13 snakes. The Actinomyces sp. was also identified by PCR of cloacal swabs of unaffected snakes (n=94) from the affected colony and two unrelated, grossly unaffected breeding colonies. In the affected colony, 65.5% of breeding animals (n=23) but only 11.9% of virgin animals (n=42) tested PCR positive, with breeding status being a significant predictor of bacterium presence (P<0.00001). This study characterizes a granulomatous mucosal disease syndrome of breeding male ball pythons associated with a novel Actinomyces. In stark contrast to male snakes, the presence of the bacterium in both breeding and virgin females was very rarely associated with clinical disease. Though additional studies are necessary, these data suggest a role for the novel bacterium in the disease process, a predilection for clinical disease in male snakes, and the potential for sexual transmission of the disease.